Hérnia de Grynfelt: uma revisão narrativa da literatura - Martins, Júlia Caramaschi (Universidade Federal de São Carlos, 2024)
Grynfelt's hernia is a rare pathology that presents as a defect in the posterolateral abdominal wall in the upper lumbar triangle. Both its diagnosis and treatment are requested due to its infrequent occurrence and anatomical complexity. What is presented is a bibliographical research of articles published between the years 2019 and 2023 focusing on surgical techniques for Grynfeltt hernia without associated complications. The search was carried out in the “PubMed” database, using the descriptor “Grynfeltt hernia”. There was no restriction due to the study methodology. Initially, 19 studies were identified, of which 11 were excluded if they did not meet the pre-established criteria (surgical management of hernias of the upper lumbar triangle without other associated pathologies). Only articles in English were selected, totaling 8 studies selected to be recorded and detailed. Among the articles, 6 case reports, 1 systematic review and 1 didactic surgical description were selected. It is concluded that Grynfelt's lumbar hernias are rare pathologies, mostly unilateral and asymptomatic, requiring high clinical suspicion for their diagnosis. Complementation with imaging examination favors surgical planning, in which different techniques (open versus laparoscopic; with mesh versus without mesh) can be used with favorable outcomes for patients.
Grynfelt's Hernia: a narrative review of the literature
Keywords: Herniorrafia; Hérnia abdominal; Revisão; CIENCIAS DA SAUDE::MEDICINA